Properties of three layer particleboard from mahang gajah (Macaranga Gigantea) / Mohd Nazir Ismail and Mohd Tarmizi Rahimi - Ismail, Mohd Nazir; Rahimi, Mohd Tarmizi (2006)
At the first time we make this project three layers particleboard uses Mahang Gajah (Macaranga Gigantea). We are uses 1.0mm and 2.0mm particle sizes for core and O.5mm for face and back. We are used 12% urea -formaldehyde. This blending, forming and by specific pressure and temperature. The strength properties will be defined by testing Modulus of Rupture (MOR), Modulus of Elasticity (MOE), Thickness Swelling (TS), Water Absorption (WA) and Internal Bonding (IB). From the result we obtained, different particle size will affect to the strength properties of three layers particleboard. it's not very suitable to make particleboard, it must be resolved for that species of wood can be use as new resource for manufacturing three layers particleboard.